Fate of Carbonates in the Earth’s Mantle (10-136 GPa) - Gao, Jing; Wu, Xiang; Yuan, Xueyin; Su, Wen (Frontiers in Earth Science, 2022)
Earth carbon cycle shapes the evolution of our planet and our habitats. As a key region of carbon cycle, subduction zone acts as a sole channel transporting supracrustal carbonate rocks down to the mantle, balancing carbon budget between the Earth’s surface and the interior, and regulating CO2 concentration of the atmosphere. How carbonates evolve at depth is thus, a most fundamental issue in understanding carbon flux and carbon sequestration mechanism in the Earth. This study reviews prominent progresses made in the field of crystal chemistry of carbonates along subduction geotherms. It clearly finds that, in addition to common carbonates in the Earth’s crust, several new polymorphs of carbonates have been discovered to be stable under high-pressure and high-temperature conditions. This opens possibilities for oxidized carbon species in the deep Earth. However, metamorphic decarbonatation and reduction reactions restrict subducting carbonates to the top-mid region of the lower mantle. Specifically, subsolidus decarbonatation in the form of carbonates reacting with silicates has been proposed as an efficient process releasing CO2 from slabs to the mantle. Besides, carbonate reduction in the metal-saturated mantle likely results in generation of super-deep diamonds and a considerable degree of carbon isotope fractionation. Review of these novel findings leads us to consider three issues in the further studies, including (1) searching for new chemical forms of carbon in the mantle, (2) determining the reduction efficiency of carbonates to diamonds and the accompanying carbon isotope fractionation and (3) concerning carbon cycle in subduction of continental crust.